2016
DOI: 10.1186/s13256-016-1018-0
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial thrombi resembling myxoma regressed after prolonged anticoagulation in a patient with mitral stenosis: a case report

Abstract: BackgroundMany cases of cardiac masses have been reported in the literature, but in this case report we described a rare case of biatrial cardiac mass that represented a challenge for diagnosis and therapy. The differentiation between cardiac masses such as thrombi, vegetations, myxomas and other tumors is not always straightforward and an exact diagnosis is important because of its distinct treatment strategy. Transthoracic/esophageal echocardiography and cardiac magnetic resonance play an important role in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…There have been reported cases of concurrent left atrial myxoma and thrombi, which required surgical excision to confirm the diagnosis [12][13]. The presence of intracardiac myxoma may present with symptoms of low flow state, which can predispose patients to thrombi formation [13,15]. We could not definitively exclude atrial myxoma in our patient.…”
Section: Discussionmentioning
confidence: 79%
“…There have been reported cases of concurrent left atrial myxoma and thrombi, which required surgical excision to confirm the diagnosis [12][13]. The presence of intracardiac myxoma may present with symptoms of low flow state, which can predispose patients to thrombi formation [13,15]. We could not definitively exclude atrial myxoma in our patient.…”
Section: Discussionmentioning
confidence: 79%
“…Atrial thrombi masquerading as myxomas have been reported in the literature, with echocardiography and cardiac magnetic resonance being among the diagnostic modalities used. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 We conducted a PubMed search for reports of left atrial thrombi misdiagnosed as myxomas and found 24 cases, 20 of which had predisposing procoagulant conditions, namely, atrial fibrillation in 11 patients, mitral stenosis in five patients, left ventricular dysfunction in three patients, and systemic lupus erythematosus in one patient. Details were not available for three patients, and one patient had undergone cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Details were not available for three patients, and one patient had undergone cardiac transplantation. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Thrombus in this situation may have identifiable causes such as deep vein thrombosis, metastasis, and mitral stenosis. [ 6 ] Thrombus is more irregular in shape. Intracardiac thrombus being more fragile usually presents with evidence of pulmonary, systemic embolism, and coronary embolism.…”
Section: Discussionmentioning
confidence: 99%